The Effect of Using Flipped Classroom Strategy on Students’ Speaking Ability - Nanda Inayah Agustiara; Rizki Amelia (Universitas Negeri Medan, 2024)
This research aims to find out the effect of using the Flipped Classroom Strategy on the speaking ability of the eighth-grade students at MTs Al-Ma’arif. The research is quantitative research with an experimental research design. Technique in collecting data is quasi-experimental. The research population were eighth-grade students of MTs Al-Ma’arif, in the academic year of 2023/2024 with a total of 37 students. There were 37 students as a sample of this research. The purposive sampling technique was used in this research. The instrument used to collect data in this research was an oral test consisting of a pre-test and a post-test. The analysis of quantitative data showed that the application of the Flipped Classroom Strategy was an effective strategy in the speaking classroom. The technique of analyzing data was an independent sample T-test through SPSS 25 and Cohen’s d formula. The results of the independent sample t-test indicated that the sig (2-tailed) value was 0.00 < 0.05 which means there was a significant difference on students’ speaking ability, and the effect size was 1.81 with a percentage of 96%. In conclusion, there is a significant effect on the speaking ability of the eighth-grade students taught by using and without using the Flipped Classroom Strategy at MTs Al-Ma’arif.